2020
DOI: 10.1021/acs.jproteome.9b00790
|View full text |Cite|
|
Sign up to set email alerts
|

Accelerated Lysis and Proteolytic Digestion of Biopsy-Level Fresh-Frozen and FFPE Tissue Samples Using Pressure Cycling Technology

Abstract: Pressure cycling technology (PCT)-assisted tissue lysis and digestion have facilitated reproducible and highthroughput proteomic studies of both fresh-frozen (FF) and formalin-fixed paraffin-embedded (FFPE) tissue of biopsy scale for biomarker discovery. Here, we present an improved PCT method accelerating the conventional procedures by about two-fold without sacrificing peptide yield, digestion efficiency, peptide, and protein identification. The time required for processing 16 tissue samples from tissues to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

6
2

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 29 publications
0
52
0
Order By: Relevance
“…al analyzed the mRNA expression of autopsies of seven lungs from COVID-19 patients and reported intussusceptive angiogenesis which may be induced by hypoxemia (Ackermann et al, 2020). Latest advances of proteomics technologies allow effective and robust analysis of formalin-fixed tissue samples (Gao et al, 2020; Zhu et al, 2019). Comparative analysis of mRNA and protein expression in tissue samples showed that proteins measured by mass spectrometry was much more stable than transcripts (Shao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…al analyzed the mRNA expression of autopsies of seven lungs from COVID-19 patients and reported intussusceptive angiogenesis which may be induced by hypoxemia (Ackermann et al, 2020). Latest advances of proteomics technologies allow effective and robust analysis of formalin-fixed tissue samples (Gao et al, 2020; Zhu et al, 2019). Comparative analysis of mRNA and protein expression in tissue samples showed that proteins measured by mass spectrometry was much more stable than transcripts (Shao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The time for SWATH measurement is 2 to 3 h per run. These sample processings and measurements are slow compared to the reported rapid protocol based on the urea-PCT-SWATH method 22 . Our protocol can process 16 samples but can only measure 10 samples per day.…”
Section: Discussionmentioning
confidence: 99%
“…Our protocol can process 16 samples but can only measure 10 samples per day. However, it should be feasible to shorten the run time of SWATH measurement according to the reported rapid protocol 22 .…”
Section: Discussionmentioning
confidence: 99%
“…PyProphet (version 2.1.3) (24) was used for statistical validation via setting the global cutoff of FDR as 0.01 at both peptide and protein levels. Protein inference was performed as described previously (25). Unless otherwise mentioned, the software parameters were kept the same for all the analyses in this study.…”
Section: Methodsmentioning
confidence: 99%